2020
DOI: 10.7759/cureus.9575
|View full text |Cite
|
Sign up to set email alerts
|

Poor Prognostic Biochemical Markers Predicting Fatalities Caused by COVID-19: A Retrospective Observational Study From a Developing Country

Abstract: Background and objectives Infections with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are rapidly spreading, posing a serious threat to the health of people worldwide, resulting in the World Health Organization officially declaring it a pandemic. There are several biochemical markers linked with predicting the severity of coronavirus disease. This study aims to identify the most effective predictive biomarker such as C-reactive protein (CRP), ferritin, lactate dehydrogenase (LDH), procalcitoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
53
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 30 publications
5
53
1
5
Order By: Relevance
“…This may be due to the fact that COVID-19 patients often develop acute kidney injury (AKI) after hospitalization and this is accompanied by a high mortality rate [1]. Another study suggested high urea and creatinine with severe patients [16], while our results also showing urea (75% vs 53%) and creatinine (64% vs 43%) in the invasive vs non-invasively ventilated groups, respectively. Thrombocytopenia was present slightly more in nonsurvived patients in our results, like previous studies suggesting consumptive coagulopathy in deceased patients leading to thrombocytopenia but thrombocytosis in survived patients [6].…”
Section: Discussionmentioning
confidence: 46%
“…This may be due to the fact that COVID-19 patients often develop acute kidney injury (AKI) after hospitalization and this is accompanied by a high mortality rate [1]. Another study suggested high urea and creatinine with severe patients [16], while our results also showing urea (75% vs 53%) and creatinine (64% vs 43%) in the invasive vs non-invasively ventilated groups, respectively. Thrombocytopenia was present slightly more in nonsurvived patients in our results, like previous studies suggesting consumptive coagulopathy in deceased patients leading to thrombocytopenia but thrombocytosis in survived patients [6].…”
Section: Discussionmentioning
confidence: 46%
“…They assessed likewise patients in survivors and non-survivor groups. They reported that there was a significant difference in TLC (p<0.001), ANC (p<0.001) and ALC (p<0.001) [10].…”
Section: Discussionmentioning
confidence: 98%
“…While Herold et al have associated mechanical ventilation most accurately with CRP (AUC: 0.860) followed by LDH, PCT, and ferritin [28]. Although, D-dimer was an effective predictor of mortality in COVID-19 specified by various studies [36,37]. Overall, mortality predictions have been mostly associated in the literature with LDH, followed by CRP, D-dimer, moderately associated with NLR and PCT, and least associated with serum ferritin [38,39].…”
Section: Discussionmentioning
confidence: 99%